2009
DOI: 10.1038/nature08027
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of the pollen self-incompatibility determinant in Papaver rhoeas

Abstract: Higher plants produce seed through pollination, using specific interactions between pollen and pistil. Self-incompatibility (SI) is an important mechanism used in many species to prevent inbreeding, and is controlled by a multi-allelic S locus1,2. “Self” (incompatible) pollen is discriminated from “non-self” (compatible) pollen, by interaction of pollen and pistil S locus components, and is subsequently inhibited. In Papaver rhoeas, the pistil S locus product is a small protein that interacts with incompatible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
154
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 195 publications
(160 citation statements)
references
References 37 publications
3
154
0
3
Order By: Relevance
“…17 In Papaver rhoeas L. (the field poppy), S-determinants are novel, highly polymorphic proteins, PrsS and PrpS. 18,19 PrsS triggers a Ca 2 þ -dependent signalling Self-incompatibility response Self-incompatibility response in incompatible pollen (Papaver rhoeas) Depolymerisation Depolymerisation followed by polymerisation and aggregation into highly stable punctate foci [27][28][29][30][31] Self-incompatibility response in incompatible pollen (Pyrus pyrifolia) A. thaliana leaves/Verticillium dahliae toxins network leading to PCD in incompatible pollen. [20][21][22] There is evidence that ROS, NO 23 and an SI-activated mitogenactivated protein kinase , p56 24 signal to PCD.…”
Section: F-actin and Microtubules Reorganise During Developmental Pcdmentioning
confidence: 99%
“…17 In Papaver rhoeas L. (the field poppy), S-determinants are novel, highly polymorphic proteins, PrsS and PrpS. 18,19 PrsS triggers a Ca 2 þ -dependent signalling Self-incompatibility response Self-incompatibility response in incompatible pollen (Papaver rhoeas) Depolymerisation Depolymerisation followed by polymerisation and aggregation into highly stable punctate foci [27][28][29][30][31] Self-incompatibility response in incompatible pollen (Pyrus pyrifolia) A. thaliana leaves/Verticillium dahliae toxins network leading to PCD in incompatible pollen. [20][21][22] There is evidence that ROS, NO 23 and an SI-activated mitogenactivated protein kinase , p56 24 signal to PCD.…”
Section: F-actin and Microtubules Reorganise During Developmental Pcdmentioning
confidence: 99%
“…However, hydropathy plot analysis indicated that these proteins may share three to four membrane-spanning domains, and may localize to the plasma membrane of papilla cells, where the interaction between pollen and stigma cells occurs. The structural features of SE proteins are similar to the predicted structure of PrpS proteins, the female determinant of SI of Papaver (Wheeler et al 2009 ), and the fl ower protein of Drosophila (Yao et al 2009 ;Brose and Neher 2009 ), which may act as a Ca 2+ channel in synaptic endocytosis (Fig. 25.11 ).…”
Section: Genes Located At or Near The S -Locus Of I Trifi Damentioning
confidence: 63%
“…PrpS has been shown to be expressed at the plasma membrane, and the predicted extracellular loop of PrpS interacts with PrsS. Use of PrpS antisense oligonucleotides in the pollen in vitro SI bioassay allowed demonstration that PrpS is involved in S -specifi c inhibition of incompatible pollen, providing evidence that it has the biological function expected (Wheeler et al 2009 ).…”
Section: The Pollen S -Locus Determinantsmentioning
confidence: 99%
“…PrpS encodes a novel, small highly hydrophobic protein with a predicted M r ~20 kDa. Examination of the PrpS sequences for nonsynonymous to synonymous ( Ka / Ks ) substitutions revealed no signifi cant difference between substitution rates in PrpS and PrsS genes (Wheeler et al 2009 ). This observation suggests that the pollen and pistil S alleles coevolved, and are likely to be equally ancient, which is an expected characteristic of S -determinants.…”
Section: The Pollen S -Locus Determinantsmentioning
confidence: 99%
See 1 more Smart Citation